RETRACTED: pH Responsive Polymer Micelles Enhances Inhibitory Efficacy on Metastasis of Murine Breast Cancer Cells - Wang, Jie; De, Gejing; Yue, Qiaoxin; Ma, Hai; Cheng, Jintang; Zhu, Guangwei; Du, Maobo; Yi, Hong; Zhao, Qinghe; Chen, Yanjun (Frontiers in Pharmacology, 2018)
A pH sensitive micellar cargo was fabricated for pH triggered delivery of hydrophobic drug paclitaxel with pH controlled drug release profiles. The size, drug loading content, and encapsulation efficiency of PTX loaded micelles were 20-30 nm, 7.5%, 82.5%, respectively. PTX loaded PELA-PBAE micelles could enhance the intracellular uptake of a model drug significantly, with increased cytotoxicity and inhibition of tumor metastasis on 4T1 cells, as confirmed by wound healing assay and tumor cells invasion assay. The expression of metastasis and apoptosis correlated proteins on 4T1 cells decreased remarkably after intervention by PTX loaded polymer micelles, as demonstrated by western blotting and quantitative reverse transcriptional-polymerase chain reaction (qRT-PCR). Our results demonstrated the pH responsive polymer micelles might have the potential to be used in the treatment of metastatic breast tumors.